Golden Years - Huffman, Felicity; Sternhagen,Frances; Szarabajka, Keith; Call, R.D.; Lauter, Ed (Hollywood, CA Paramount Pictures, 2013)
This made-for-TV mini-series from the notorious horror writer centers upon a hapless old janitor who begins undergoing incredible physical changes after he is accidentally covered with experimental chemicals following a laboratory mishap. Now the government will stop at nothing to get him back
112810
Keywords: Chemical laboratories; Explosions; Rejuvenation